A field investigation of passive radiative cooling under Hong Kong's climate. (June 2017) - Tso, C.Y.; Chan, K.C.; Chao, Christopher Y.H.
Abstract: This paper discusses the feasibility of cooling using radiation under Hong Kong's hot and humid climate. Three different designs of a passive radiative cooler were studied in this work. The three designs include non-vacuum, and vacuum with seven potassium chloride (KCl) IR-Pass windows as well as one system with a single KCl IR-Pass window. The coolers were examined during daytime and night time operation as well as under different sky conditions, such as clear, cloudy and partly cloudy. Investigation was mainly based on the temperature difference between the radiative cooler and ambient air. The experimental results showed that the passive radiative cooler with seven KCl windows and the cooler design without vacuum provided a satisfactory cooling effect at night (i.e. the ambient air temperature was reduced by about 6–7 °C), but the coolers could not produce a cooling effect during daytime under any of Hong Kong's weather conditions. The same results were obtained for the passive radiative cooler with the single KCl window during daytime operation. However, the cooling capacity of the passive radiative cooler design without vacuum under a clear night sky achieved 38 W/m 2 . Highlights: A radiative cooler with three thermal designs is investigated experimentally. The experiments are carried out in Hong Kong's hot and humid climate. The radiative cooler can provide a satisfactory cooling effect at night. The designs are unable to provide the cooling effect during daytime. The cooling capacity of 38 W/m 2 is achieved at a clear sky night.